Trier le vivant urbain. Entre héritages et normes, des pratiques toujours teintées de sélection - Aurélien Judic; Sabine Bognon (VertigO, 2023)
The relationship between those involved in the management of living organisms and biodiversity is a central issue in the future of urban spaces: not only do the majority of humankind lives in or under the influence of an urban space, but urbanization is one of the main causes of biodiversity erosion on a global scale. This article examines the issues of sorting and caring for the living, which organize and influence the changing relationship between managers and, ultimately, city dwellers, towards urban biodiversity. Firstly, we explore the heritage of the different management working cultures, through a review on hygienism and its evolutions (post-hygienism and neo-hygienism). We then analyze regulations and the ways in which managers apply or fail to apply them. Finally, we present the results of a survey of public and semi-public stakeholders in the management of urban public spaces in several French local authorities. It reveals a diversity of representations and even narratives that produce different ways of legitimizing the sorting of non-human beings within the city.